Quantitative determination of loss in yield of black pepper (Piper nigrum L.) in Kannur District (Kerala, India) - PRABHAKARAN, P V (Journal of Spices and Aromatic Crops, 1997)
A method for estimation of yield loss (including stand loss) in black pepper (Piper nigrum) due to various factors was developed. The method was applied for estimating the loss in yield of black pepper due to incidence of pests, diseases and drought in Kannur District (Kerala, India) during 1989-1992. The average annual yield loss in black pepper due to these factors was around 33 per cent. The major contributors towards stand loss, was foot rot caused by Phythopthora capsici contributing to 9 per cent loss followed by drought. Among the causal factors contributing to yield loss the most disastrous was incidence of poilu beetle (Longitarsus nigripennis) which accounted for about 13 per cent loss followed by fungal poilu caused by Colletotrichum gleosporioides. The percentage avoidable loss in yield by adopting plant protection measures was estimated to be around 43 per cent.